Оценка влияния психологического состояния на гормональный профиль женщин во время беременности - Сюсюка, В. Г.; Syusyuka, V. G.; Сюсюка, Володимир Григорович (My University, 2015)
Based on investigation of 65 pregnant women with gestation term of 26–32 weeks it was found that more than 90% of pregnant women have trait anxiety. Based on results of hormonal profile estimation there was found that pregnant women with high and middle level of the state anxiety have indicators of both cortisol and prolactin were statistically higher (p > 0.05) than appropriate indicators of pregnant women with low state anxiety level.
Psychological assessmentof state for hormonal profile of women during pregnancy